Oral Health Education for Pediatric Nurse Practitioner Students. Issue 5 (24th August 2018) - Golinveaux, Jay; Gerbert, Barbara; Cheng, Jing; Duderstadt, Karen; Alkon, Abbey; Mullen, Shirin; Lin, Brent; Miller, Arthur; Zhan, Ling
Abstract : The aim of this study was to evaluate whether an interdisciplinary, multifaceted oral health education program delivered to pediatric nurse practitioner students at the University of California, San Francisco, would improve their knowledge, confidence, attitudes, and behaviors regarding the provision of oral health assessments, consultations, referrals, and services to young children during well‐child visits. Thirty pediatric nurse practitioner students were included in the study. Participants completed a written survey before and after receiving an interdisciplinary educational intervention that included didactic education, simulation exercises, and clinical observation by a pediatric dental resident. Between pre‐intervention and post‐intervention, a significant improvement was seen in the pediatric nurse practitioners' knowledge of oral health topics (p<0.001), confidence when providing oral health counseling (p<0.001), and attitudes about including oral health counseling in their examinations (p=0.006). In the post‐intervention survey, 83 percent of the subjects reported having incorporated oral examinations into their well‐child visits. Our study suggests that providing an interdisciplinary oral health educational program for pediatric nurse practitioner students can improve their knowledge, confidence, attitudes, and behaviors regarding the incorporation of oral health care services during routine well‐child visits.